Biological Impact of Ocean Acidification in the Canadian Arctic: Widespread Severe Pteropod Shell Dissolution in Amundsen Gulf - Niemi, Andrea; Bednaršek, Nina; Michel, Christine; Feely, Richard A.; Williams, William; Azetsu-Scott, Kumiko; Walkusz, Wojciech; Reist, James D. (Frontiers in Marine Science, 2021)
Increasing atmospheric CO2, cold water temperatures, respiration, and freshwater inputs all contribute to enhanced acidification in Arctic waters. However, ecosystem effects of ocean acidification (derived from anthropogenic and/or natural sources) in the Arctic Ocean are highly uncertain. Zooplankton samples and oceanographic data were collected in August 2012–2014 and again in August 2017 to investigate the pelagic sea snail, Limacina helicina, a biological indicator of the presence and potential impact of acidified waters in the Canadian Beaufort Sea. Between 2012 and 2014 L. helicina abundance ranged from <1 to 1942 Ind. m–2, with highest abundances occurring at stations on the Canadian Beaufort Shelf in 2012. The majority of individuals (66%) were located between 25 and 100 m depth, corresponding to upper halocline water of Pacific origin. In both 2014 and 2017, >85% of L. helicina assessed (n = 134) from the Amundsen Gulf region displayed shell dissolution and advanced levels of dissolution occurred at all stations. The severity of dissolution was not significantly different between 2014 and 2017 despite the presence of larger individuals that are less prone to dissolution, and higher food availability that can provide some physiological benefits in 2014. Corrosive water conditions were not widespread in the Amundsen Gulf at the time of sampling in 2017, and aragonite undersaturation (Ωar < 1) occurred primarily at depths >150 m. The majority of dissolution was observed on the first whorl of the shells strongly indicating that damage was initiated during the larval stage of growth in May or early June when sea ice is still present. Evidence of shell modification was present in 2014, likely supported by abundant food availability in 2014 relative to 2017. The proportion of damaged L. helicina collected from coastal embayments and offshore stations is higher than in other Arctic and temperate locations indicating that exposure to corrosive waters is spatially widespread in the Amundsen Gulf region, and periods of exposure are extreme enough to impact the majority of the population.